Selective ribosome profiling reveals a role for SecB in the co-translational inner membrane protein biogenesis - Eismann, Lena; Fijalkowski, Igor; Galmozzi, Carla Verónica; Koubek, Jiří; Tippmann, Frank; Van Damme, Petra; Kramer, Günter (Cell reports, 2022)
The chaperone SecB has been implicated in de novo protein folding and translocation across the membrane, but it remains unclear which nascent polypeptides SecB binds, when during translation SecB acts, how SecB function is coordinated with other chaperones and targeting factors, and how polypeptide engagement contributes to protein biogenesis. Using selective ribosome profiling, we show that SecB binds many nascent cytoplasmic and translocated proteins generally late during translation and controlled by the chaperone trigger factor. Revealing an uncharted role in co-translational translocation, inner membrane proteins (IMPs) are the most prominent nascent SecB interactors. Unlike other substrates, IMPs are bound early during translation, following the membrane targeting by the signal recognition particle. SecB remains bound until translation is terminated, and contributes to membrane insertion. Our study establishes a role of SecB in the co-translational maturation of proteins from all cellular compartments and functionally implicates cytosolic chaperones in membrane protein biogenesis.